Thoughts on the long-term digital preservation of scholarly journals - Kim, Kihong (Science Editing, 2022)
Online publishing has become a dominant trend in the publishing of scientific, technical, and medical (STM) journals. Almost all STM journals already publish online, and the proportion of those that publish online-only is increasing rapidly. Online publishing obviously requires a completely different approach to preserving journal content. All storage devices are based on magnetic phenomena and are governed by the laws of physics. Stored digital information can spontaneously become erroneous or corrupted over time, and this problem can be worsened when the ambient magnetic field is stronger and the temperature is higher. Therefore, digital information needs to be carefully stored in an environment where the temperature and the ambient magnetic field are well-controlled and must be backed up periodically. Many difficult technical problems are also associated with managing complex file structures and formats as a database grows. These tasks require considerable effort and expenses. Thus, it seems natural to ask whether journal publishers or the institutions that keep their digital materials have sustainable plans and resources to preserve journals for a long period of time